The investigation of the effects of some variables in the playoff games played in Turkey women's basketball super league between 2013-2017 on winning and losing - (:unkn) unknown (NATL OLYMPIC COMMITTEE UKRAINE, KHARKOV REGIONAL BRANCH, 2018)
Purpose: The aim of this research was to reveal positive and negative effects of the parameters causing to win or lose the game by investigating playoff series games played in Turkey Women's Basketball Super League between 2013-2017. Material: The data used in the research was obtained from end of game statistics given by Turkish Basketball Federation (TBF). The variables measured (2-point field-goals percentage, 3-point field-goals percentage, free throw percentage, offensive rebound, defensive rebound, assist, steal, turnover, block, and free throws) were analyzed by Logistic Regression Analysis test method according to the winner and loser teams (P<0.05), and the goodness of fit of the test model was measured by Hosmer and Lemeshow Test (Hosmer-Lemeshow goodness of fit test). Results: Hosmer and Lemeshow goodness of fit test result was found 0.724. The model was seen to be relatively small model (-2 Log likelihood, 139.731) Cox & Snell R Square showed that it explained 47% of the variance, and Nagelkerke R Square showed that it explained 63% of the variance. Conclusions: According to the results of the research, it was found that a one-unit increase in 2-point field-goals percentage, 3-point field-goals percentage, offensive rebound, defensive rebound, steal and turnover variables had significant effects of winning and losing the game.
Keywords: Basketball; winners; losers; playoff; STATISTICS